Farmer-based financing of operations in the Niger Valley irrigation schemes - Abernethy, Charles L.; Sally, Hilmy; Lonsway, K.; Maman, C. (International Water Management Institute, 2000)
Presents the results of case-studies of the functioning of four pump-based irrigation systems in the Niger River Valley. Prospects for sustainability are analyzed, especially in the light of the government's policy of promoting irrigator organizations to take over responsibilities for operation and maintenance.